FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KALA II LAMA DI RUANG BERSALIN RSUD H. DAMANHURI BARABAI KALIMANTAN SELATAN - maulida sari (Indonesian Journal of Midwifery Scientific, 2023)
Background:. Prolonged labor is one of several causes of death for mothers and newborns. Long second stage of labor is the second stage which lasts more than 2 hours in primi and more than 1 hour in multiparas. Objective: to determine the factors related to the Old Stage II Event in the Delivery Room of the H. Damanhuri Barabai Hospital, South Kalimantan. Methods: This study used an analytic survey design using data registers in the maternity ward of H. Damanhuri Barabai Hospital with a case control design. Results: The study showed that 176 respondents (50%) gave birth to mothers who experienced a long second stage of labor, the factors associated with a long second stage were age, parity, his, baby's weight, and fetal position with a p value <0.05, while anemia was not related. with the occurrence of the old second stage with p > α (0.05)Conclusion: pregnant women should carry out routine checks so that they can maintain their pregnancy properly and detect it quickly during delivery in the handling of long second stage events Keywords: Maternity, old second stage, age, parity, his, anemia, baby's weight, fetal position